Pop-up Storybook Media Development for Cultivating Peace-loving Characters in Early Childhood - Febi Pebriani; Amelia Vinayastri (EduBasic Journal: Jurnal Pendidikan Dasar, 2022)
Character formation is a necessary provision for early childhood to uphold morals and control themselves from the adverse effects of today's technology when they grow up. In practice, media use for character introduction still looks monotonous in early childhood. Therefore, it is inevitable that the researchers' creative solutions develop interesting and emerging media. Pop-up storybooks are learning media compiled by combining text and 3D image illustrations to resemble the real ones. Developing a pop-up storybook also aims to help educators introduce characters to early childhood, especially peace-loving characters. This study, thus, conducted the five steps of the ADDIE model as its development process: analysis, design, development, implementation, and evaluation. This study employed an assessment instrument in the form of a media expert validation sheet, material, and character. In addition, media testing was conducted by Tahfidz Al-Quran Yamabi Kindergarten and Marga Laksana Kindergarten for children aged groups A and B. The analysis results highlighted that this book was feasible and valid. Furthermore, this book was feasible to be applied in instilling peace-loving characters in early childhood. For this reason, teachers are expected to periodically use pop-up storybooks and the like to instill other characters